2005
DOI: 10.1063/1.1914764
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast proton transfer of 1-hydroxy-2-acetonaphthone: Reaction path from resonance Raman and transient absorption studies

Abstract: The intramolecular degrees of freedom contributing to the ultrafast excited-state intramolecular proton transfer of 1-hydroxy-2-acetonaphthone are determined. Thereto, resonance Raman studies are combined with transient absorption measurements with 30-fs time resolution. Enhanced Raman intensity is found in coordinates that are dominantly associated with deformations and bond length changes in the naphthalene chromophore. This indicates that the primary changes after the optical excitation are a geometric rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 33 publications
11
84
1
Order By: Relevance
“…Theoretical study of 1-hydroxy-2-acenaphthone (1H2AN) at HF [39] and DFT [40] levels showed very similar energy variation for the S 0 and S 1 surfaces where there is facile proton transfer in the excited state. A recent time-resolved study showed that the ESIPT process in 1H2AN and related compound lies in the sub 100-fs range [41]. Douhal et al reported the existence of different low energy conformers Fig.…”
Section: Quantum Chemical Calculationmentioning
confidence: 98%
“…Theoretical study of 1-hydroxy-2-acenaphthone (1H2AN) at HF [39] and DFT [40] levels showed very similar energy variation for the S 0 and S 1 surfaces where there is facile proton transfer in the excited state. A recent time-resolved study showed that the ESIPT process in 1H2AN and related compound lies in the sub 100-fs range [41]. Douhal et al reported the existence of different low energy conformers Fig.…”
Section: Quantum Chemical Calculationmentioning
confidence: 98%
“…Lochbrunner et al used transient absorption (TA) experiments and Raman spectroscopy to determine the ESIPT rate of HAN in liquid to be around 30 fs. 38 They also observed characteristic oscillations in TA experiments, which were assigned to the vibrational modes contributing to the ESIPT. Molecular dynamics simulation has also been performed to show the relevance of those modes to ESIPT.…”
Section: Introductionmentioning
confidence: 95%
“…the very initial sub-20 fs dynamics. [44 -46] The analysis of these modes in conjunction with normal mode calculations is a prerequisite for the elucidation of the structural changes [47] involved in the reaction path from the Franck-Condon state towards the thermally equilibrated excited (S 1 ) or intermediate state (S ICT ). Therefore, it is to be expected that the resonantly enhanced modes play an important role for the primary reaction dynamics in PChlide.…”
Section: Structural Dynamics In Pchlide Upon Electronic Excitationmentioning
confidence: 99%